Design of differential resistive measuring system and its applications - Abdul Wahab, Deji; Khan, Sheroz; Chebil, Jalel (IIUM Press, 2011)
Differential resistive systems are easily designed using potentiometric sensors. They usually contain two sensing resistances and a common movable terminal. This circuit can be used to sense a number of scenario; such as the liquid level in a tank, biomedical applications in determining the expansion and contraction of the muscles, the amount of bend in a bimetallic strip, the expansion and contraction in roads and railways, cracks in building for civil application, the penetration of signal in buildings for telecommunication and communication engineering applications, the voltage level in complex circuit. Since sensors with high sensitivity and good resolution are required for industrial applications, hence the need for this cheap and affordable sensor's design. Also, their output must have linear responses, that is, the output produced should be linearly proportional to the parameters of interest [1]. This chapter deals with the design of a differential resistive measuring sensor with low cost, low power consumption, with small size and improved overall performance of the circuit implanted in human body in order to generate voltage, current whose frequency, duty cycle is proportional to the physical parameters of interest